SYNTHESIS OF PRECIPITATED CALCIUM CARBONATE FROM BLOOD COCKLE SHELL (ANADARA GRANOSA) AS RAW MATERIAL - Wilanda, Sendyka
Preparation of precipitated calcium carbonate could be the best way to improve the quality of calcium carbonate in the industrial world. Utilization of these precipitates are commonly found in several industry, like paints, rubber, plastics, toothpaste, and as additives in papermaking. During this time, the industry relies heavily on calcium oxide as a natural carbonate raw materials, it is necessary to develop other alternative materials that can support the quality improvement of calcium carbonate. This is done by using raw materials of solid waste in the form of shell carbonate blood cockles Anadara granosa. This material contained a huge of calcium carbonate, make it as a potential alternative material manufacturing calcium carbonate precipitates. The purpose of this study is to synthesize calcium carbonate precipitates at room temperature, then proceed with the characterization of products. The research method started with calcined powders of crushed shells at a temperature of 9000 C. Calcination results dissolved in water to form calcium hydroxide. Carbondioxide flowed on it, with the parameters of concentration and the influence of solvent volume to produce calcium carbonate precipitate. The final step is to characterize product by it’s degree of brightness, FTIR, XRD, SEM, and BET. The results obtained from this study indicate that the synthesis of precipitated calcium carbonate at room temperature with a concentration of 3.57 M solution of calcium hydroxide produce a brightness of 90.8 % relatives to CaCO3 standard, CO2 flow rate measured by the flow of HCl 6 M at 1.35 mL/ minute on producing CO2 from NaHCO3. The presence of carbonates is shown in wave numbers 1444 cm-1 on IR spectra. Based on the results of XRD, precipitated CaCO3 has a crystal structure of calcite. SEM measurement results show a mixture of spherical and cubes particle shapes with a size of 0,1- 0,5 ?m. Through the BET , shown that the spesific surface area and radius pores of powders obtained by increasing 162,14 % and 0,21 % respectively.